Social Capital Role in Solving Land Degradation in Tulis Watershed - Kusbiantoro, Ari; Awang, San Afri; Gunawan, Totok; Maryudi, Ahmad (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2016)
The research aimed at studying social capital role in land degradation solving of Tulis watershed. The parameters under observation were social capital (trust, norm, and social networking), social-economic condition, and land management in Tulis watershed. The parameters were achieved by using data triangulation principle. The analysis used was Structural Equation Modeling (SEM). The model used five variables, which were social capital (X1), society structure (X2), land using conflict (Y1), land management strategy (Y2), and land degradation (Y3). Perspective of social capital theory could be used to explain the interaction between society socio-cultural behaviors and land degradation of Tulis watershed. The model proved that society structure with effective social capital, low conflict in land using, and good land management strategy afforded to decrease land degradation of Tulis watershed.